Protein hydrolysates derived from residual after polysaccharide extraction of Chlorella vulgaris biomass improves yield and quality of baby leaf lettuce - Annamaria Di Serio; Giovanna Aquino; Francesco Del Prete; Francesca Sansone; Emanuela Salviati; Manuela Giovanna Basilicata; Michele Manfra; Pietro Campiglia; Domenico Ronga; Giacomo Pepe (Scientific Reports)
Abstract The world is facing new challenges related to climate change and agriculture and is called to ensuring higher crop yield and quality following the concept of food safety, security and efficient resource use. One of the possible strategies could be the valorisation of agro-industrial by-products for the production of biostimulants. The aim of the present work was to assess the action of different protein hydrolysates (PHs) derived by residues of Chlorella vulgaris biomass as biostimulant on lettuce (Lactuca sativa L.), monitoring the agronomic, physiological and qualitative traits, from seed germination to the harvest. The application of biostimulants derived by PHs had interesting results on lettuce, highlighting several positive effects on the investigated parameters. Additionally, the metabolite profiles of baby leaf lettuce were investigated. In particular, was recorded an improvement of the qualitative traits, as flavonoids and anthocyanins contents, and physiological parameters such as the reduction of stomatal conductance. Our results demonstrated that plants treated with PHs obtained through trypsin-induced hydrolysis of Chlorella vulgaris biomass (TPH-1000) exhibited the highest content of bioactive compounds and antioxidant activity compared to those treated with water alone or with a commercial biostimulant. Additionally, plants treated with pepsin protein hydrolysates (PPH-1000) showed significant improvements in agronomic, physiological, and qualitative performance. These results suggest that biostimulants derived from agro-industrial by-products represent a promising and resource-efficient approach to support agricultural productivity and food quality in the context of climate change and the need for more sustainable practices.